Ville Nouvelle et Attractivité des Centres Commerciaux en Algérie: Etude de Cas des Centres Commerciaux de la Ville Nouvelle Ali Mendjeli de Constantine - Rehail, Tayeb (جامعة الأمير عبد القادر للعلوم الإسلامية - كلية أصول الدين, 2021)
يقترح هذا النص النظر في الكيفية التي استطاعت من خلالها المدينة الجديدة علي منجلي بقسنطينة، اكتساب نوع من الشهرة بينما انجزت في بداية المطاف كنوع من الامتداد البسيط للمدينة الأم وظيفتها استقبال برامج إعادة الإسكان بالولاية. كما يقترح كذلك النظر في الكيفية التي استطاعت من خلالها التحول من فضاء طارد إلى فضاء جذاب وتنافسي بخلق إضافات نوعية للإقليم. وكيف تمكنت من إنشاء ليس فقط مساحات من أجل الاستهلاك ولكن أيضاً مساحات للاستهلاك والترفيه.
This text proposes to see how the new city Ali Mendjeli of Constantine, whereas it was initially conceived as a simple extension of the mother city by proposing a land base which could claim to become the receptacle of all the programs of (re) housing in the capital of the wilaya, has succeeded in forging a kind of notoriety over time. And how was she able to get through certain cogs, from a repulsive space to an attractive, and competitive space, while creating a kind of gentrification of the territory. And how she was able to create not only spaces for consumption but also spaces to consumption.
Keywords: تخطيط المدن -- التوزيع العمراني -- المرافق العامة -- مراكز التسوق -- الجزائر